ICTeachMUPO: An Evaluation of Information E-Learning Module System for Faculty and Students - Urera Jr., Flaviano L.; Balahadia, Francis F. (International Journal of Computing Sciences Research; Vol 3 No 1 (2019): Vol 3, No 1, 2019)
Purpose – This study explored the utilization of ICT tools and resources in developing ICTeachMUqPO. This information e-learning module system is a web-based application designed to support the academic needs of both faculty and students, in particular to track learning progress. Method – The proponents conducted a group discussion and collaboration with the end users and reviewed literature on faculty development and related studies to gather preliminary information. They also identified all software and hardware specifications necessary in developing the system through a survey. The descriptive method of research was employed in designing the system evaluation process. Judgmental or purposive sampling was used in selecting the respondents (n=113) who answered the evaluation survey.  Result – The system evaluation survey was patterned after ISO 25010 and consisted of the following components: functionality, usability, reliability, performance, security, compatibility and supportability. The overall rating of the system was 4.11, which indicated a “very good” grade.  The portability test showed that the system can run on any computing platform using different web browser applications. Conclusions – The result of the system evaluation by the respondent implied that the system’s overall internal and external performance exhibited consistency and met the compliance requirements set by the developers. Recommendation – The authors recommend that teachers and students undergo ICT capability training to get the most out of the functionalities of the ICTeachMUqPO e-learning management system. The school administrators may provide support in terms of enhanced accessibility of facilities, higher internet bandwidth allocation and better network infrastructure. The proponents suggest that further research be conducted using other variables, taking another direction such as assessing the learning outcome and behavior of the students using the system. Research Implication – E-learning or learning management systems can save faculty members time when preparing for their classes. The system can make use of additional features but in its present form it can already be a very useful educational tool to both the teacher and the student users. Making use of this technology could be an impetus for transitioning to other methods of instruction, such as online teaching.